DWT and MFCC based human emotional speech classification using LDA - Murugappan, Muthusamy, Dr.; Nurul Qasturi Idayu, Baharuddin; Jeritta, S (Institute of Electrical and Electronics Engineers (IEEE), 2012)
Link to publisher's homepage at http://ieeexplore.ieee.org/